Polarization of Indonesian Society during 2014-2020: Causes and Its Impacts toward Democracy - Wasisto Raharjo Jati (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2022)
Polarization was widely used in a large number of publications on Indonesian political studies from 2014 to 2020. This term particularly refers to the divisive society condition because of different political preferences. Previously, polarization is rare to use to frame Indonesian electoral competition since both parties and candidates counted on ideological spectrum. Since the personalization of politics have been flourishing recently, it drives identity to be marker when it comes to evaluating the candidates. This condition, consequently, makes the election is not merely political competition for power but emotional competition for lives. For the last six years, there were three major elections, including the 2014 Presidential Election, 2017 Jakarta Gubernatorial Election, and 2019 Presidential Election. These three elections had a significant factor in polarizing society at that given time. They specifically referred to the two leading figures that represented the two stark political identity symbols. However, after 2018, the polarization of society itself seemed under control since the ruling regime coalitions and their social groups and allies worked together. It was meant to manage the effect of polarization and also to corner the opposition groups. While the clashes of views still exist, the situation would be worse if the 3 elections had not happened.